2010
DOI: 10.1128/aac.00358-10
|View full text |Cite
|
Sign up to set email alerts
|

Amodiaquine Resistance in Plasmodium falciparum Malaria in Afghanistan Is Associated with the pfcrt SVMNT Allele at Codons 72 to 76

Abstract: Mutations in the Plasmodium falciparum genes pfcrt and pfmdr1 are selected by amodiaquine treatment in Africa. To examine the importance of these mutations in amodiaquine-treated Asian parasites, we determined pre-and posttreatment genotypes for amodiaquine treatment failures from a clinical trial in Afghanistan. The pfcrt codon 72 to 76 haplotype SVMNT was present in all samples tested, both before and after treatment. Amodiaquine did not clearly select for any pfmdr1 genotype, but a novel mutation, pfmdr1 N8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 18 publications
4
77
3
Order By: Relevance
“…The pfmdr1 locus is known to be present in multiple copies in some drug-resistant parasites, particularly those resistant to mefloquine (13,28). As part of this analysis, we observed different genotypes for the pfmdr1 locus in the Dd2 parasite and confirmed the presence of the newly reported pfmdr1 N86F mutation in Dd2 (4,9). This demonstrates the ability of these assays to detect mutations among loci subject to copy number variation, which has been implicated in some drug-resistant parasites (11,18,22).…”
Section: Resultssupporting
confidence: 64%
“…The pfmdr1 locus is known to be present in multiple copies in some drug-resistant parasites, particularly those resistant to mefloquine (13,28). As part of this analysis, we observed different genotypes for the pfmdr1 locus in the Dd2 parasite and confirmed the presence of the newly reported pfmdr1 N86F mutation in Dd2 (4,9). This demonstrates the ability of these assays to detect mutations among loci subject to copy number variation, which has been implicated in some drug-resistant parasites (11,18,22).…”
Section: Resultssupporting
confidence: 64%
“…3 Furthermore, several recent studies indicate that the SVMNT mutations may be sufficient to confer resistance to amodiaquine. 11,12 Although the current ACT regimen used in Sri Lanka is artemether-lumefantrine, the high prevalence of the SVMNT haplotype found in Sri Lanka cautions against the widespread adoption of amodiaquinebased ACTs in the country.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Furthermore, the haplotypes observed in codons 72-76 have been associated with different fitness costs, coresistance to amodiaquine, and geographic origins. [10][11][12] A previous study has investigated these markers in Sri Lanka, finding that, among 76 samples collected from patients in the Mannar district of Northern Province in 2002 and 2004, 76.3% had the T76 mutation. 7 However, no published studies from outside the Mannar district have yet measured the change in haplotype frequencies in Sri Lanka over time.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies in falciparum malaria-endemic areas have suggested that K76T mutant parasites are linked to chloroquine resistance in both in vitro and in vivo trials [3][4][5][6][7]. The K76T mutation has also been found to be associated with amodiaquine resistance and predictive treatment failure for both chloroquine and amodiaquine [8][9][10]. The association of the N86Y mutation in the pfmdr1 gene in chloroquine resistance has been debated; some studies suggest that its presence along with pfcrt mutations can cause higher levels of chloroquine resistance [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%